A feedback regulatory loop between HIF‐1α and miR‐21 in response to hypoxia in cardiomyocytes. Issue 17 (28th June 2014) - Liu, Yang; Nie, Honggang; Zhang, Kuikui; Ma, Dan; Yang, Guang; Zheng, Zhilei; Liu, Kai; Yu, Bo; Zhai, Changlin; Yang, Shuang
Abstract : Accumulating evidence suggests that hypoxia‐inducible factor 1α (HIF‐1α) regulates numerous miRNAs and is crucial for cellular response to hypoxia. However, the relationship between HIF‐1α and miR‐21 in hypoxic cardiomyocytes is little known. We found that hypoxia induced HIF‐1α and miR‐21 expression. HIF‐1α knockdown increased cell apoptosis and reduced miR‐21 expression. Furthermore, we found that HIF‐1α transcriptionally enhanced miR‐21 promoter activity by binding to its promoter, which required the recruitment of CBP/p300. In addition, we found that miR‐21 inhibition increased cell apoptosis and reduced HIF‐1α expression, and modulated the PTEN/Akt pathway. Our results indicate that HIF‐1α‐miR‐21 feedback contributes to the adaptation of cardiomyocytes to hypoxia, and has potential as therapeutic target for myocardial ischemia. Abstract : HIF‐1α and miR‐21 are induced under hypoxia. HIF‐1α increases miR‐21 expression via binding to its promoter, in turn, miR‐21 upregulates HIF‐1α expression. HIF‐1α and miR‐21 contribute to the adaptation of the cell to hypoxia by inhibiting apoptosis.